Leucocytes and Th-associated cytokine profile of HIV-leishmaniasis coinfected patients attending the Abuja Teaching Hospital, Nigeria - Abdullahi, Idris Nasir; Emeribe, Anthony Uchenna; Adekola, Hafeez Aderinsayo; Muhammad, Habiba Yahaya; Ahmad, Abdurrahman El-fulaty; Anka, Abubakar Umar; Haruna, Shamsuddeen; Oderinde, Bamidele Soji; Mohammed, Yusuf; Shuwa, Halima Ali; Babayo, Adamu (Journal of Medical Science, 2020)
Introduction. T-helper cells (Th)-1& -2 cytokines homeostasis control orpredict clinical outcome of infected persons, especially those with HIV /AIDS. This case-control study evaluated the leucocytes differentials, TNF-alpha, interleukin (IL)-2 and -10 levels among HIV infected persons with serological evidence of leishmaniasis attending University of Abuja Teaching Hospital, Nigeria.Material and Methods. Blood samples from 28 HIV infected persons who had Leishmania donovani rK39 and IgG positive (group 1), 30 age- & -sex matched HIV infected persons without Leishmania antibodies (group 2) and 30 apparently healthy persons without HIV and Leishmania antibodies (group 3). Full blood counts, TNF alpha, IL-2 and -10 levels were analyzed using automated hematology analyzer and ELISA, respectively. Structured questionnaires were used to collate biodata and clinical presentations of participants.Results. Ten (35.7%) participants in group 1 were on ART, 15 (50%) in group 2 were on ART, while group 3 were ART naïve. There were significantly higher values in basophil (4.4 ± 2.5%) and eosinophil counts (12.9 ± 3.8%) in HIV/leishmania coinfected persons (p ˂ 0.005). However, other white cells subpopulation was significantly lower in HIV/leishmania co-infected participants (p ˂ 0.05). There was significantly reduced CD4+ T cell counts ([119 ± 26 versus 348 ± 63 versus 605 ± 116 cells/mm3]), TNF-alpha ([36.82 ± 8.21 versus 64.67 ± 12.54 versus 254.98 ± 65.59 pg/mL]) and IL-2 levels ([142.14 ± 20.91 versus 507.6 ± 84.42 versus 486.62 ± 167.87 pg/mL]) among HIV/Leishmania co-infected participants compared to group 2 and group 3 participants, respectively. However, higher IL-10 level (80.35 ± 14.57 pg/mL) was found in HIV/Leishmania co-infected participants as opposed to the HIV mono-infected (62.2 ± 10.43 pg/mL) and apparently healthy persons (23.97 ± 4.88 pg/mL) (p ˂ 0.001).Conclusion. Eosinophil, basophil counts and serum IL-10 level were high in HIV/Leishmania coinfected persons, demonstrating parasite-induced hypersensitivity and immunosuppression.